Kurzivna pisava v Madame Bovary - Gacoin-Marks, Florence (Primerjalna književnost, 2010)
The use of italics is one of the means Flaubert employs to create narrative heteroglossia in Madame Bovary, with its intricate interplay of the voices of the narrator, of the characters and of the provincial bourgeoisie, and it has attracted considerable scholarly attention. After exploring the possible reasons why the author might have chosen to highlight certain features using italics, we concluded that it was useful to establish a typology of his different uses of italic script in order to attempt a systematic and comprehensive study of this Flaubertian stylistic device for the purpose of evaluating translations of the novel.
Keywords: Flaubert, Gustave, 1821-1880; francoska književnost; French literature; pripovedne tehnike; polifonija; literarni prevodi; prevodi v slovenščino